2014
DOI: 10.2147/copd.s59962
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of airflow limitation in outpatients with cardiovascular diseases in Japan

Abstract: Background and objectivesCardiovascular disease (CVD) and chronic obstructive pulmonary disease (COPD) commonly coexist and share common risk factors. The prevalence of COPD in outpatients with a smoking history and CVD in Japan is unknown. The aim of this study was to determine the proportion of Japanese patients with a smoking history being treated for CVD who have concurrent airflow limitation compatible with COPD. A secondary objective was to test whether the usage of lung function tests performed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…However, the few studies confirm that reduced pulmonary function is associated with cardiovascular risk factors [1,19]. Multivariate models have also confirmed the independent association of cardiovascular lifestyles, high-risk conditions and lower levels of FEV 1 and FVC.…”
Section: Discussionmentioning
confidence: 91%
“…However, the few studies confirm that reduced pulmonary function is associated with cardiovascular risk factors [1,19]. Multivariate models have also confirmed the independent association of cardiovascular lifestyles, high-risk conditions and lower levels of FEV 1 and FVC.…”
Section: Discussionmentioning
confidence: 91%
“…The data from this study regarding the symptoms of patients with undiagnosed airflow limitation have already been published. 8 …”
Section: Methodsmentioning
confidence: 99%
“…The Hi-Checker has been previously demonstrated to be an accurate alternative to the conventional spirometer. 8 FEV 1 and FEV 6 were measured prior to bronchodilator use. Subjects performed forced expiration for 6 seconds until reproducible FEV 6 values were obtained (the difference between the two highest FEV 6 values was not more than 0.10 L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 31.3% did not receive any clinical intervention (smoking cessation advice and/or drug administration). Another study determined the proportion of Japanese patients with smoking histories being treated for cardiovascular disease who had concurrent airflow limitation compatible with COPD 23. The study (N=995) indicated that a quarter of outpatients with cardiovascular disease had COPD, but in almost all of them, the condition was undiagnosed.…”
Section: Epidemiology and Treatment Of Copd In Japanmentioning
confidence: 99%